Financial soundness indicators : analytical aspects and country practices - Sundararajan, V....[et al.] (IMF WashingtonUS, 2002)
Focuses on selected analytical aspects of defining and analyzing financial soundness indicators (FSIs). Discusses country practices in the use, compilation, and dissemination of FSIs.